Dynamic Analysis of Sandwich Cylindrical Shell - Cabanska-Placzkiewicz, K. (Проблемы прочности, 2000)
We present dynamic analysis of cylindrical
shells and study new mechanical effects in
distribution of stresses, strains and
displacements. Cylindrical shells are studied in
the framework of Kirchhoff-Love hypothesis
and the refined Timoshenko model. Выполнен динамический анализ цилиндрических оболочек и изучены новые механические
эффекты в распределении напряжений, деформаций и перемещений. Цилиндрические оболочки
рассматриваются на основе гипотезы Кирхгофа-Лява и уточненной модели Тимошенко. Проведено динамічний аналіз циліндричних оболонок та розглянуто нові
механічні ефекти в розподіленні напружень, деформацій і переміщень.
Циліндричні оболонки розглядаються на основі гіпотези Кірхгофа-Лява й
уточненої моделі Тимошенка.